THE INFLUENCE OF ORGANIZATIONAL JUSTICE ON EMPLOYEE ORGANIZATIONAL COMMITMENT AT CLASS IIA PALU CORRECTIONAL INSTITUTION - Pramodatiara, Ade Novita; Kusmiyanti, Kusmiyanti (Universitas Nusa Cendana, 2025)
Perceptions of justice can be a key determinant of organizational commitment at Class IIA Palu Prison, which in turn affects the overall performance and effectiveness of correctional facilities in achieving their organizational goals. The objective of this research is to determine the influence of organizational justice on the organizational commitment of employees of Class IIA Palu Prison. The research was conducted at the Class IIA Palu Prison, with the population consisting of all employees. A total sample of 104 respondents was selected using the saturated sampling method. The researcher employed a quantitative method, using a questionnaire as the research instrument with a 5-point Likert scale. The analytical methods used included descriptive analysis, factor analysis, and regression analysis. The results showed that organizational justice positively influences organizational commitment. The relationship between the variables is strongly positive, and the coefficient of determination indicates that the organizational justice variable explains 72.2% of the organizational commitment variable. It is hoped that the results of this study can serve as a reference and consideration for correctional leaders and employees in Indonesia. Keywords: Organizational Justice; Organizational Commitment; Prison